Empathy, Pain and Attention: Cues that Predict Pain Stimulation to the Partner and the Self Capture Visual Attention - Wu, Lingdan; Kirmse, Ursula; Flaisch, Tobias; Boiandina, Ganna; Kenter, Anna; Schupp, Harald T. (Frontiers in Human Neuroscience, 2017)
Empathy motivates helping and cooperative behaviors and plays an important role in social interactions and personal communication. The present research examined the hypothesis that a state of empathy guides attention towards stimuli significant to others in a similar way as to stimuli relevant to the self. Sixteen couples in romantic partnerships were examined in a pain-related empathy paradigm including an anticipation phase and a stimulation phase. Abstract visual symbols (i.e., arrows and flashes) signaled the delivery of a Pain or Nopain stimulus to the partner or the self while dense sensor event-related potentials (ERPs) were simultaneously recorded from both persons. During the anticipation phase, stimuli predicting Pain compared to Nopain stimuli to the partner elicited a larger early posterior negativity (EPN) and late positive potential (LPP), which were similar in topography and latency to the EPN and LPP modulations elicited by stimuli signaling pain for the self. Noteworthy, using abstract cue symbols to cue Pain and Nopain stimuli suggests that these effects are not driven by perceptual features. The findings demonstrate that symbolic stimuli relevant for the partner capture attention, which implies a state of empathy to the pain of the partner. From a broader perspective, states of empathy appear to regulate attention processing according to the perceived needs and goals of the partner.